Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.7895/ijadr.246
|View full text |Cite
|
Sign up to set email alerts
|

Fieldworker effects on substance use reporting in a rural South African setting

Abstract: Aims: Fieldworkers capturing reports of sensitive behaviors, such as substance use, may influence survey responses and represent an important factor in response validity. We explored the effects and interaction of fieldworker and respondent characteristics (age and gender) in substance (tobacco and alcohol) use reporting. We aim to further the literature on conditional social attribution effects on substance use reporting in the context of South Africa, where accurate estimates of modifiable risk factors are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(37 reference statements)
0
4
0
Order By: Relevance
“… 27 While we showed no association with alcohol use, our sample also had low self-reported use of alcohol, with 80% reporting not drinking in the past month, which may be due to response bias. 49 Given the limited employment opportunities in our setting, 28 a higher risk of hypertension among employed individuals may represent those more likely to be exposed to workplace-related stress and other behavioural factors such as diet 50 51 that may differ from those not employed.…”
Section: Discussionmentioning
confidence: 99%
“… 27 While we showed no association with alcohol use, our sample also had low self-reported use of alcohol, with 80% reporting not drinking in the past month, which may be due to response bias. 49 Given the limited employment opportunities in our setting, 28 a higher risk of hypertension among employed individuals may represent those more likely to be exposed to workplace-related stress and other behavioural factors such as diet 50 51 that may differ from those not employed.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not have data on parental history of hypertension to use in our hypertension probability model, which may have reduced the discriminatory capability of our model ( 28 ). In addition, we only had a binary alcohol consumption measure, which may be subject to reporting error or bias that could have affected the predictive capability of the Wand et al model used in this analysis ( 57 ). Future studies should address how to minimize error and biases in the measurement of alcohol consumption in this study context.…”
Section: Discussionmentioning
confidence: 99%
“…Another strength is the inclusion of a large sample of consecutive RLS patients, with a sex ratio similar to the one reported for RLS prevalence in epidemiological data (Berger et al, 2004 ; Didriksen et al, 2017 ; Hening et al, 2004 ; Högl et al, 2005 ; Kim et al, 2019 ). A possible limitation is that all patients were interviewed by a female investigator: interviewer’s gender has been reported to cause a bias in responses about sensitive experiences or behaviours (which are reported more frequently to women by women (Harling et al, 2019 ) and to female voices by men (Dykema et al, 2012 )), or substance abuse (which seems to be reported more often to men by both women and men; Heeb & Gmel, 2001 ; Houle et al, 2019 )). Although men and women talk about the same when in same‐gender dyads, women talk less while talking to men, whereas men talk more when talking to women than when talking to men (Mulac, 1989 ).…”
Section: Discussionmentioning
confidence: 99%